Pathogenicity and molecular characterization of a GI-19 infectious bronchitis virus isolated from East China - Wu, Qi; Xu, Mengcheng; Wei, Dengle; Zhang, Xuehua; Li, Ding; Mei, Mei (Frontiers in Veterinary Science, 2024)
Infectious bronchitis virus (IBV) is responsible for avian infectious bronchitis, a disease prevalent in countries with intensive poultry farming practices. Given the presence of multiple genotypic strains in China, identifying the regionally dominant genotypes is crucial for the implementation of effective prevention and control measures. This study focuses on the IBV strain CK/CH/WJ/215, isolated from a diseased commercial chicken flock in China in 2021. The CK/CH/WJ/215 isolate was genetically characterized through complete S1 sequence analysis. Phylogenetic comparisons were made with prevalent vaccine strains (H120, LDT3-A, and 4/91). Glycosylation patterns in the S1 protein were also analyzed. Pathogenicity was assessed in 7-day-old specific-pathogen-free chicks, monitoring morbidity, mortality, and tissue tropisms. Phylogenetic analysis clustered the CK/CH/WJ/215 isolate within the GI-19 lineage. Identity with the vaccination strains H120, LDT3-A, and 4/91 was low (75.7%, 78.6%, and 77.5% respectively). Novel glycosylation sites at positions 138 and 530 were identified compared to H120 and LDT-A. The isolate demonstrated nephropathogenic characteristics, causing 100% morbidity and 73.3% mortality in SPF chicks, with broader tropisms in tissues including trachea, lungs, kidneys, and bursa of Fabricius. Comprehensive genetic and pathological investigations revealed significant differences between the CK/CH/WJ/215 isolate and common vaccine strains, including novel glycosylation sites and a strong multiorgan infective capability. These findings are crucial for understanding the evolutionary dynamics of IBV and developing more effective prevention and control strategies.